Metabolomic analysis of breath volatile organic compounds reveals unique breathprints in children with inflammatory bowel disease: a pilot study. Issue 5 (16th July 2014) - Patel, N.; Alkhouri, N.; Eng, K.; Cikach, F.; Mahajan, L.; Yan, C.; Grove, D.; Rome, E. S.; Lopez, R.; Dweik, R. A.
Summary Background Breath testing is becoming an important diagnostic method to evaluate many disease states. In the light of rising healthcare costs, is important to develop a simple non‐invasive tool to potentially identify paediatric patients who need endoscopy for suspected inflammatory bowel disease (IBD). Aim To analyse exhaled volatile organic compounds (VOCs) and investigate the presence of a unique breath patterns to differentiate paediatric patients with (IBD) from healthy controls. Methods A cross‐sectional, single‐centre study included paediatric IBD patients and healthy controls (age range, 5–21 years). The diagnosis of IBD was confirmed by endoscopic, histological and radiographic data. Exhaled breath was collected and analysed using a selective ion flow tube mass spectroscopy (SIFT‐MS) to identify new markers or patterns of IBD. Results One hundred and seventeen patients (62 with IBD and 55 healthy controls) were included in the study. Linear discriminant analysis and principle component analysis of mass scanning ion peak data demonstrated 21 pre‐selected VOCs correctly classify patients with IBD or as healthy controls; P < 0.0001. Multivariable logistic regression analysis further showed three specific VOCs (1‐octene, 1‐decene, (E)‐2‐nonene) had excellent accuracy for predicting the presence of IBD with an area under the curve (AUC) of 0.96 (95% CI: 0.93–0.99). No significant difference in VOCs was found between patients with Crohn's disease or ulcerative colitis, and no significant correlation was seen with disease activity. Conclusion These pilot data support the hypothesis that a unique breathprint potentially exists for paediatric IBD in the exhaled metabolome.